Psychological Aspect of Rehabilitation and Return to Sport Following Lower Limb Injuries - Jan Marusic; Petra Dolenc; Nejc Sarabon (Montenegrin Sports Academy, 2020)
In addition to an athlete's physical abilities, his or her mental state is also vital for optimal recovery and a successful return to sport after an injury. The purpose of the present review was to determine which psychological factors affect the success of rehabilitation and return to sport following the most frequent musculotendinous thigh injuries (hamstrings, hip adductors, knee extensors), and to present the main psychological screening tools and interventions that can aid the athlete's rehabilitation and return to sport. A systematic review of the literature did not reveal any relevant results related to those injuries; therefore, the search was expanded to whole lower limb injuries, which showed that several different psychological factors could have a significant impact on an athlete's rehabilitation and decision to return to sport. It can be presumed that these factors can similarly affect the post-injury process for thigh injuries, which should be considered when planning the rehabilitation programme. Systematically implementing psychological screening and psychological interventions (if needed) into the already established rehabilitation protocols would be reasonable for optimizing an athlete's recovery and for helping with the decision to return to sport.